A study on promotional tools that applied by TM SME Perak in achieving sales and win back VOIP customer / Siti Najwa Sharir Zaaba - Sharir Zaaba, Siti Najwa (2009)
Heavy competition in telecommunication industry will make Telekom Malaysia work harder to compete with their competitors to keep and retain their customer especially business customer. This situation may encourage and give challengers to the company to maintain their reputation and performance. I believe that this company especially TM SME Perak have their own plan to achieve their objective. This paper serves to discuss on the performance of the promotional tools that TM SME Perak applied in order to achieve sales and win back VOIP customer. So in this case study, I will share on what I have observed about the promotion program that this company used in achieving the objective. Beside that, these studies also will view on the issue or problems that arise during the implementation of TM SME Perak promotional activities. At last the purpose of this proposal is served to provide suggestion and recommendation that can be applied by this company in future. In preparing this proposal, I found that this company facing with challengers and problem especially in winning sales and win back their losing customer. There has a gap during implementing their promotional activities because the current promotional activities that applied by TM SME Perak are different with the theory. So at the end of the study, I recommend some solution and ideas that can be used in order to solve the problem that facing by this company.